High-performance high-nickel ternary material and preparation method and application thereof
By using ammonium phosphate additives to form a modified layer and reducing alkaline substances in the preparation of high-nickel ternary materials, the problem of residual alkali on the surface of the material is solved, the cycle stability and conductivity of the material is improved, the battery life is extended, and the battery life is simplified. The preparation process realizes the preparation of materials with high performance, high circulation and low residual alkali.
Patent Information
- Application Number
- CN202411210505.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
There is a problem of surface alkali residue during the preparation process of high nickel ternary materials, which affects the processing and electrochemical properties of the materials, resulting in an increase in the defect rate and shortening of the cycle life during the battery manufacturing process, and the existing removal methods are difficult to ensure the stability of the material. and recyclability.
The mixture of high-nickel ternary precursor and lithium source is sintered under an oxygen-rich atmosphere, and reacted with ammonium phosphate additive under negative pressure to form a LixM(PO4)y modified layer to protect the surface of the material and reduce electrolyte corrosion. The content of alkaline substances is reduced by reacting NH4+ ions with residual lithium ions.
It significantly improves the cycle stability and conductivity of high-nickel ternary materials, extends the service life of the battery, reduces the residual alkali content, improves the initial charging and discharge efficiency and overall performance of the battery, and simplifies the preparation process and is suitable for batches. Production and environmental protection.
Smart Images

Figure BDA0005020197340000061 
Figure BDA0005020197340000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and more specifically, to a high-performance high-nickel ternary material and a preparation method and application thereof. Background Art
[0002] Among the many positive electrode materials for lithium-ion batteries, ternary positive electrode materials (usually nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), etc.) are favored due to their high energy density and relatively low manufacturing cost. In particular, high-nickel ternary materials are considered to be key materials for the development of next-generation high-performance lithium-ion batteries due to their high specific capacity and energy density.
[0003] However, there are some technical challenges in the preparation process of high-nickel ternary materials, one of the most prominent problems is the residual alkali problem on the surface of the material. This problem seriously affects the processing performance and electrochemical properties of the material, limiting its application in the field of battery manufacturing. During the preparation process of high-nickel ternary materials, especially during the sintering stage, a certain amount of alkaline substances may remain on the surface of the material, such as lithium hydroxide (LiOH), lithium carbonate (Li2CO3), etc. These residual alkali substances mainly come from impurities in the raw materials or chemical reactions during the sintering process.
[0004] Residual alkali on the surface will increase the water absorption of the material during the pulping and coating process, and it is easy to react with the binder and solvent to form a "jelly"-like substance. This phenomenon not only affects the uniform coating of the material, but may also cause uneven thickness of the battery pole pieces, increasing the defective rate in the battery manufacturing process. Residual alkali will accelerate the decomposition of the electrolyte and reduce the interfacial stability of the battery. This not only reduces the initial capacity of the battery, but also accelerates the capacity decay during the battery cycle, affecting the cycle life and energy retention rate of the battery. Under high temperature and high pressure conditions, residual alkali substances may trigger side reactions inside the battery, increase the internal pressure of the battery, and even cause safety problems such as battery bloating and explosion.
[0005] In order to reduce the residual alkali on the surface of high-nickel ternary materials, researchers are exploring more efficient and environmentally friendly solutions. The existing technology discloses a method of removing residual lithium ions in ternary materials using fluorinated phosphate additives, but this method is difficult to ensure the stability of the material and cannot improve its recyclability, and the residual LiOH and Li2CO3 are still high.
[0006] Therefore, developing a preparation method that can effectively remove residual alkali and improve the cycle performance of high-nickel ternary materials has important research significance and application value. Summary of the invention
[0007] The present invention aims to overcome the deficiencies of the prior art and provide a method for preparing a high-performance high-nickel ternary material to prepare a high-performance high-nickel ternary material with excellent cyclability, low residual alkali and high capacity.
[0008] Therefore, the primary purpose of the present invention is to provide a method for preparing high-performance high-nickel ternary materials.
[0009] Another object of the present invention is to provide a high-performance high-nickel ternary material prepared by the above preparation method.
[0010] Another object of the present invention is to provide an application of the above-mentioned high-performance high-nickel ternary material.
[0011] To achieve the above object, the present invention adopts the following technical solutions:
[0012] The present invention provides a method for preparing a high-performance high-nickel ternary material, comprising the following steps:
[0013] The mixture of the high-nickel ternary precursor and the lithium source is sintered in an oxygen-rich atmosphere at 700-800° C. for 8-15 hours to obtain a high-nickel ternary material, wherein the molar ratio of the high-nickel ternary precursor to the lithium source is 1:1.01-1.10;
[0014] The high-nickel ternary material is mixed with an ammonium phosphate additive, and reacted at 500 to 700° C. and a negative pressure of -0.07 to -0.09 MPa for 4 to 8 hours to obtain the high-performance high-nickel ternary material; wherein the ammonium phosphate additive is (NH4) x M(PO4) y , said (NH4) x M(PO4) y Wherein M is at least one of Al, Mn, Cr, W, Y, Nb, Ti, Mg, Sb, V, W, Zr, Co, and Ni, wherein 1≤x≤4, 1≤y<4;
[0015] The weight fraction of the ammonium phosphate additive is 0.2% to 1.0% of the weight of the high-nickel ternary material.
[0016] High-nickel ternary material is a material with a high molar fraction of nickel (Ni) in the positive electrode material of lithium-ion batteries, usually higher than 60%, or even more than 90%. It is the main development trend of ternary positive electrode materials in the future.
[0017] The oxygen-rich atmosphere is a gas atmosphere with an oxygen content greater than 90%.
[0018] The present invention has been found through research that the chemical formula is (NH4) x M(PO4) y Ammonium phosphates play a key role in improving the circularity of materials.
[0019] When (NH4) x M(PO4) y M(PO4) y Li on the surface of high nickel ternary cathode material + When the reaction occurs, the compound Li x M(PO4) y .Li x M(PO4) y A modified layer is formed on the surface of the material particles, which can protect the active material from direct erosion by the electrolyte. Certain components in the electrolyte may react with the active material, resulting in damage to the material structure and degradation of performance. x M(PO4) y Layers can reduce this direct contact, thereby extending the service life of the material. During the charge and discharge process, the material will experience volume expansion and contraction. x M(PO4) y The presence of the layer can act as a buffer layer to reduce the structural stress caused by the insertion and extraction of lithium ions, thereby maintaining the structural integrity of the material and improving the cycle stability. Reducing the chemical corrosion of the electrolyte on the material is crucial to maintaining the long-term stability and cycle performance of the material, helping to improve the cycle performance of the material, extend the service life of the battery, and improve its overall performance.
[0020] Secondly, during the first charge and discharge process, Li x M(PO4) y It can release active lithium ions, which can directly participate in electrochemical reactions and improve the initial charge and discharge efficiency of the material. The release of active lithium ions helps to increase the initial capacity of the battery, that is, the first efficiency.
[0021] In addition, Li x M(PO4) y The formation of can also improve the conductivity of high nickel ternary materials. Good conductivity is crucial to the charge and discharge performance of battery materials because it can reduce the resistance to electron transmission and improve the charge and discharge rate and efficiency of the battery.
[0022] At the same time, NH4 in ammonium phosphate + Ions can interact with residual lithium ions (OH - 、CO3 2- ) reacts to generate NH3H2O and (NH4)2CO3. These products decompose at high temperatures to produce NH3, CO2 and H2O, which are effectively removed by the exhaust system, thereby significantly reducing the residual alkali content in the material. This process not only improves the performance of the material, but also effectively prevents the pollution of the environment by the exhaust gas through the treatment of the exhaust gas absorption device.
[0023] Preferably, the (NH4) x M(PO4) y It is at least one of (NH4)V(PO4)2, (NH4)Cr(PO4), (NH4)W(PO4), (NH4)3Y(PO4)2 or (NH4)Nb(PO4)2.
[0024] Preferably, the high-nickel ternary precursor is nickel-cobalt-aluminum hydroxide or nickel-cobalt-manganese hydroxide.
[0025] Specifically, the molecular formula of the nickel-cobalt-manganese hydroxide is Ni a Co b Mn 1-a-b (OH)2; the molecular formula of the nickel-cobalt-aluminum hydroxide is Ni a Co b Al 1-a-b (OH)2; wherein 0.80≤a<1, 0<b≤0.20.
[0026] More preferably, the nickel-cobalt-manganese hydroxide is Ni 0.8 Co 0.1 Mn 0.1 (OH)2 or Ni 0.9 Co 0.5 Mn 0.5 (OH)2; the nickel-cobalt-aluminum hydroxide is Ni 0.8 Co 0.1 Al 0.1 (OH)2 or Ni 0.9 Co 0.5 Al 0.5 (OH)2.
[0027] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, lithium acetate, lithium oxalate, and lithium dihydrogen phosphate.
[0028] Preferably, the heating rate of the sintering is 3-6°C / min.
[0029] Preferably, the heating rate of the mixing reaction with the ammonium phosphate additive is 10-20° C. / min.
[0030] Specifically, the gas generated in the method is extracted and sent to a tail gas absorption device for treatment.
[0031] Preferably, the oxygen-rich atmosphere is an atmosphere with an oxygen content of more than 90%.
[0032] The present invention also protects the application of the above-mentioned high-performance high-nickel ternary material in lithium-ion batteries.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention provides a method for preparing a high-nickel ternary material. By adjusting sintering conditions and adding an ammonium phosphate additive, the prepared high-performance high-nickel ternary material has the properties of excellent cyclability, low residual alkali and high capacity.
[0035] The method for preparing high-performance high-nickel ternary materials of the present invention is simple, suitable for batch operation, does not generate wastewater in the process, is environmentally friendly, saves the wastewater treatment process, and effectively reduces manufacturing costs. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0037] 1. Experimental methods
[0038] Example 1 A high-performance high-nickel ternary material and its preparation method
[0039] S1. Mixing: Mix the high nickel ternary precursor and lithium salt evenly
[0040] Specifically, a certain amount of high-nickel ternary precursor and lithium source are put into a high-speed mixer and mixed evenly; wherein the molar number of high-nickel ternary precursor: the molar number of lithium salt is 1:1.05; the lithium source is lithium hydroxide; the high-nickel ternary precursor is nickel-cobalt-aluminum hydroxide, and its molecular formula is Ni 0.8 Co 0.1 Al 0.1 (OH)2;
[0041] S2. Sintering:
[0042] The uniformly mixed powder is placed in a box furnace with an oxygen content greater than 90%, heated to 780°C at a heating rate of 5°C / min, and kept warm for 12 hours to obtain a high-nickel ternary positive electrode material sintered once.
[0043] S3. Reaction:
[0044] The high-nickel ternary material sintered once in S2 and a certain proportion of additives (NH4)V(PO4)2 are added to the mixer and mixed evenly. The weight of the added additives is 0.5% of the weight of the high-nickel ternary material. Then the mixed materials are put into the plow dryer, heated to 600℃ at a rate of 15℃ / min for reaction, and the plow dryer is evacuated to -0.08MPa. The evacuated gas is connected to the exhaust gas treatment device to treat the exhaust gas; after 6 hours of reaction, a high-performance high-nickel ternary positive electrode material is obtained.
[0045] Example 2 A high-performance high-nickel ternary material and its preparation method
[0046] The scheme is the same as that of Example 1, except that the molar number of lithium salt in S1 is 1:1.01; the temperature in S2 is raised to 700°C and kept warm for 10 hours; the temperature in S3 is raised to 500°C for reaction, the negative pressure is reduced to -0.07MPa, and the reaction is carried out for 4 hours. The weight of the added additive is 0.2% of the weight of the high-nickel ternary material.
[0047] Example 3 A high-performance high-nickel ternary material and its preparation method
[0048] The scheme is the same as that of Example 1, except that the molar number of lithium salt in S1 is 1:1.10; the temperature in S2 is raised to 800°C and kept warm for 12 hours; the temperature in S3 is raised to 700°C for reaction, the negative pressure is reduced to -0.09 MPa, and the reaction is carried out for 8 hours. The weight of the added additive is 1.0% of the weight of the high-nickel ternary material.
[0049] Example 4 A high-performance high-nickel ternary material and its preparation method
[0050] The same scheme as Example 1, except that the high nickel ternary precursor in S1 is Ni 0.9 Co 0.05 Al 0.05 (OH)2.
[0051] Example 5 A high-performance high-nickel ternary material and its preparation method
[0052] The same scheme as Example 1, except that the high nickel ternary precursor in S1 is Ni 0.9 Co 0.05 Mn 0.05 (OH)2.
[0053] Example 6 A high-performance high-nickel ternary material and its preparation method
[0054] The same scheme as Example 1, except that the high nickel ternary precursor in S1 is changed to Ni 0.8 Co 0.1 Mn 0.1 (OH)2.
[0055] Example 7 A high-performance high-nickel ternary material and its preparation method
[0056] The same scheme as in Example 1, except that the additive in S3 is (NH4)Cr(PO4).
[0057] Example 8 A high-performance high-nickel ternary material and its preparation method
[0058] The same scheme as in Example 1, except that the additive in S3 is (NH4)W(PO4).
[0059] Example 9 A high-performance high-nickel ternary material and its preparation method
[0060] The solution is the same as that of Example 1, except that the additive in S3 is (NH4)3Y(PO4)2.
[0061] Example 10 A high-performance high-nickel ternary material and its preparation method
[0062] The solution is the same as that of Example 1, except that the additive in S3 is changed to (NH4)Nb(PO4)2.
[0063] Example 11 A high-performance high-nickel ternary material and its preparation method
[0064] S1. Mixing: Mix the high nickel ternary precursor and lithium salt evenly
[0065] Specifically, a certain amount of high-nickel ternary precursor and lithium source are put into a high-speed mixer and mixed evenly; wherein the molar number of high-nickel ternary precursor: the molar number of lithium salt is 1:1.05; the lithium source is lithium hydroxide; the high-nickel ternary precursor is nickel-cobalt-aluminum hydroxide, and its molecular formula is Ni 0.8 Co 0.1 Al 0.1 (OH)2;
[0066] S2. Sintering:
[0067] The uniformly mixed powders were placed in a box furnace with an oxygen content of 20%, heated to 500° C. at a heating rate of 10° C. / min, and kept warm for 2 hours to obtain a high-nickel ternary positive electrode material sintered once.
[0068] S3. Reaction:
[0069] Same as step S3 of embodiment 1.
[0070] Comparative Example 1 A high-performance high-nickel ternary material and its preparation method
[0071] The solution is the same as that of Example 1, except that the amount of the additive (NH4)V(PO4)2 added in S3 is 0.
[0072] Comparative Example 2 A high-performance high-nickel ternary material and its preparation method
[0073] The solution is the same as that of Example 1, except that the weight of the additive (NH4)V(PO4)2 in S3 is 0.1% of the weight of the high-nickel ternary material.
[0074] Comparative Example 3 A high-performance high-nickel ternary material and its preparation method
[0075] The solution is the same as that of Example 1, except that the weight of the additive (NH4)V(PO4)2 in S3 is 1.1% of the weight of the high-nickel ternary material.
[0076] Comparative Example 4 A high-performance high-nickel ternary material and its preparation method
[0077] The same scheme as in Example 1, except that the temperature in S3 is raised to 400° C. for reaction.
[0078] Comparative Example 5 A high-performance high-nickel ternary material and its preparation method
[0079] The same scheme as in Example 1, except that the temperature in S3 is raised to 800° C. for reaction.
[0080] Comparative Example 6 A high-performance high-nickel ternary material and its preparation method
[0081] The solution is the same as that of Example 1, except that the negative pressure in S3 is pumped to -0.06 MPa.
[0082] Comparative Example 7 A high-performance high-nickel ternary material and its preparation method
[0083] The solution is the same as that of Example 1, except that the negative pressure in S3 is pumped to -0.10 MPa.
[0084] Comparative Example 8 A high-performance high-nickel ternary material and its preparation method
[0085] The same scheme as in Example 1, except that the reaction in S3 is for 3 h.
[0086] Comparative Example 9 A high-performance high-nickel ternary material and its preparation method
[0087] The same scheme as in Example 1, except that the reaction in S3 is carried out for 9 hours.
[0088] The performance test indicators of the high-performance high-nickel ternary materials of the embodiments and comparative examples of the present invention are as follows:
[0089] Residual alkali (Li2CO3 / ppm);
[0090] Residual alkali (LiOH / ppm);
[0091] First efficiency of 0.2C discharge at button battery (%): Test of button battery;
[0092] Discharge capacity at 0.2C (mAh / g): Test of button-type battery;
[0093] 1C button battery 1C100 cycle capacity retention rate (%): Test made into button battery.
[0094] 2. Experimental results
[0095] The performance test results of the high-performance high-nickel ternary materials of each embodiment and comparative example according to the above-mentioned method of the present invention are as follows:
[0096] Table 1.
[0097]
[0098]
[0099] As can be seen from Table 1, the high-performance high-nickel ternary materials prepared in the embodiments of the present invention all have high initial efficiency, stability and cycle performance, and low residual alkali. Among them, the high-nickel ternary positive electrode material prepared in Example 1 exhibits the lowest residual alkali content, and at the same time performs best in terms of capacity and cycle performance. In Example 2 and Example 3, the upper and lower limits of the proportion of additives were adjusted respectively. Compared with Example 1, the residual lithium content of the material is higher, and the capacity and cycle performance are both reduced. This further confirms the significant effect of the additive ratio on material properties; Example 4 replaces the high-nickel ternary precursor with Ni 0.9 Co 0.05 Al 0.05 (OH)2, the precursor has a higher nickel content, which theoretically will cause a higher residual alkali. However, through the additive, the residual alkali and cycle performance of the material are slightly lower than those of other embodiments, but the overall performance is still significantly improved, indicating that the performance of the material can be improved to a certain extent by reasonably selecting the precursor and additive; Example 5 and Example 6, respectively select the high nickel ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Ni 0.8 Co 0.1 Mn 0.1 (OH)2, the material performance is consistent with that of Example 1; Examples 7 to 10 replace different (NH4) x M(HPO4) y The improvement effect of material properties is equivalent to that in Example 1, indicating that the use of additives containing different metals mentioned in the present invention can also effectively improve the comprehensive performance of high-nickel ternary positive electrode materials.
[0100] In Comparative Example 1, without the use of additives, the residual alkali content, capacity and cycle performance of the material are significantly lower than those in the embodiment, indicating that the additive plays a key role in improving the material performance; in Comparative Examples 2 and 3, the amount of additives used is insufficient or excessive, resulting in the residual alkali content, capacity and cycle performance of the material being inferior to those in the embodiment, further emphasizing the importance of the amount of additives to material performance; in Comparative Examples 4 to 9, the parameters are set too low or too high, which will also result in the residual alkali content of the material being inferior to the embodiment or the capacity and cycle performance being inferior to the embodiment, indicating the importance of parameter optimization in the material preparation process.
[0101] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a high-performance high-nickel ternary material, characterized in that: The following steps are involved: The mixture of the high-nickel ternary precursor and the lithium source is sintered in an oxygen-rich atmosphere at 700-800° C. for 8-15 hours to obtain a high-nickel ternary material, wherein the molar ratio of the high-nickel ternary precursor to the lithium source is 1:1.01-1.10; The high-nickel ternary material is mixed with an ammonium phosphate additive, and reacted at 500 to 700° C. and a negative pressure of -0.07 to -0.09 MPa for 4 to 8 hours to obtain the high-performance high-nickel ternary material; wherein the ammonium phosphate additive is (NH4) x M(PO4) y , said (NH4) x M(PO4) y Wherein M is at least one of Al, Mn, Cr, W, Y, Nb, Ti, Mg, Sb, V, W, Zr, Co, and Ni, wherein 1≤x≤4, 1≤y<4; The weight fraction of the ammonium phosphate additive is 0.2% to 1.0% of the weight of the high-nickel ternary material.
2. The method according to claim 1, characterized in that The (NH4) x M(PO4) y It is at least one of (NH4)V(PO4)2, (NH4)Cr(PO4), (NH4)W(PO4), (NH4)3Y(PO4)2 or (NH4)Nb(PO4)2.
3. The method according to claim 1, characterized in that The weight fraction of the ammonium phosphate additive is 0.2% to 1.0% of the weight of the high-nickel ternary material.
4. The method according to claim 1, characterized in that: The high-nickel ternary precursor is nickel-cobalt-aluminum hydroxide or nickel-cobalt-manganese hydroxide. The molecular formula of the nickel-cobalt-manganese hydroxide is Ni a Co b Mn 1-a-b (OH)2; the molecular formula of the nickel-cobalt-aluminum hydroxide is Ni a Co b Al 1-a-b (OH)2; wherein 0.80≤a<1, 0<b≤0.
20.
5. The method according to claim 4, characterized in that The nickel-cobalt-manganese hydroxide is Ni 0.8 Co 0.1 Mn 0.1 (OH)2 or Ni 0.9 Co 0.05 Mn 0.05 (OH)2; the nickel-cobalt-aluminum hydroxide is Ni 0.8 Co 0.1 Al 0.1 (OH)2 or Ni 0.9 Co 0.05 Al 0.05 (OH)2.
6. The method according to claim 1, characterized in that The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, lithium acetate, lithium oxalate, and lithium dihydrogen phosphate.
7. The method according to claim 1, characterized in that The gas generated in the method is extracted and sent to a tail gas absorption device for treatment.
8. The method according to claim 1, characterized in that: In the method, the heating rate of the ammonium phosphate additive mixing reaction is 10-20° C. / min.
9. A high-performance high-nickel ternary material, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. Use of the high-performance high-nickel ternary material according to claim 9 in a lithium-ion battery.
